Confirmed long‐term safety and efficacy of prophylactic treatment with BAY 94–9027 in severe haemophilia A: final results of the PROTECT VIII extension study. Issue 3 (5th April 2021) - Reding, Mark T.; Pabinger, Ingrid; Holme, Pal Andre; Poulsen, Lone; Negrier, Claude; Chalasani, Pavani; Maas Enriquez, Monika; Wang, Maria; Meijer, Karina; Mancuso, Maria Elisa; Lalezari, Shadan
Abstract: Introduction: The phase 2/3 PROTECT VIII main study demonstrated efficacy and safety of BAY 94–9027 (damoctocog alfa pegol; Jivi ® ), a B‐domain‐deleted recombinant factor VIII (FVIII), site‐specifically PEGylated to extend its half‐life. Aim: To report the final efficacy and safety data for BAY 94–9027 from the PROTECT VIII extension. Methods: Previously treated males aged 12–65 years with severe haemophilia A (FVIII <1%) who completed the multicentre, open‐label PROTECT VIII main study were eligible for the extension. Patients received either on demand or prophylaxis treatments (30‒40 IU/kg twice weekly [2 × W], 45‒60 IU/kg every 5 days [E5D], or 60 IU/kg every 7 days [E7D]) and could switch to any prophylaxis regimen (variable frequency) as needed. Annualised bleeding rates (ABR), zero bleeds and safety outcomes were included in this final analysis. Results: At extension completion, patients (n = 121) received BAY 94–9027 for a median (range) total time of 3.9 (0.8–7.0) years. Median (Q1; Q3) total ABR was 1.49 (0.36; 4.80) for prophylaxis patients (n = 107), compared with 34.09 (20.3; 36.6) for on‐demand patients (n = 14). Median total ABRs for 2 × W (n = 23), E5D (n = 33), E7D (n = 23) and variable frequency (n = 28) groups were 1.57, 1.17, 0.65 and 3.10, respectively. Of prophylaxis patients, 20.6% were bleed‐free during the entire extension (median time, 3.2 years) and 50.0% were bleed‐free during the last 6 months. No patient developed FVIII inhibitors. No deaths or thrombotic events were reported. Conclusions: Efficacy and safety of BAY 94–9027 was confirmed, with extension data supporting its use as a long‐term treatment option for patients with haemophilia A.